The influence of activated coconut charcoal-based abrasives on the surface of dental enamel - Feitosa, Fernanda Alves [UNESP]; Santos, Laura Chaves [UNESP]; Barbieri, Ana Amélia [UNESP]; Teixeira, Symone Cristina [UNESP] (FapUNIFESP (SciELO), 2024)
Introduction: Activated charcoal-based products have been marketed as teeth whiteners and are widely used by the population without any quality control or studies on their impact on dental structure. Objective: The objective of this study was to evaluate the effect of brushing with powdered coconut-based products on the roughness and color of human dental enamel. Material and method: To this end, 40 enamel samples with 6mm diameter were stained with coffee for 36 hours. Initial roughness readings (Ra and Rz) and color (L* a * b*) were performed. The specimens were divided into 4 groups (n = 10): Control Group: Colgate Total 12 toothpaste; CBP Group: Activated Coconut Charcoal Powder, Black Pearl Tooth Powder; CAC Group: Activated Coconut Charcoal Powder, Activated Charcoal Tooth Whitening Powder; Group BS: Sodium bicarbonate powder. The specimens were submitted to abrasive cycles for brushing simulation (945, 4.050 and 49.275 cycles), and upon completion of these cycles, new measurements of color and roughness were taken. A 1-factor ANOVA analysis was performed to analyze the color variation and roughness data, followed by the Tukey test. Result: There was no statistical difference between the initial and final roughness in any of the groups studied. For the color data, there was no statistical difference for the L* coordinate for any group. For the coordinates a * and b* there was a difference for all groups between the initial period and all the others. Conclusion: Even after the one-year period brushing simulation, the surface roughness of the enamel of none of the products studied was affected. The color of the enamel after the accomplishment of the abrasive cycles occurred in a similar way in the experimental groups based on activated coconut charcoal and conventional toothpaste.
Influência de abrasivos a base de carvão de coco ativado sobre a superfície do esmalte dentário
Keywords: charcoal; color perception; Dental enamel; tooth abrasion; toothbrushing